The uniqueness of SMA Plus Muthahhari Bandung in character education through the development of spiritual intelligence of students - Muhammad Iskandar Suhifatullah; Wangsih Wangsih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to reveal data about the uniqueness of SMA Plus Muthahhari Bandung in the implementation of character education through the development of students' spiritual intelligence. This research is considered important for finding an effective student character education system. This is bearing in mind that character education in schools in general has not shown maximum results, and even tends to fail when viewed from the rampant deviant or immoral behavior of students and society as an educational output. This study used a descriptive qualitative method; therefore, the researcher became the main instrument by using interview techniques, observation and documentation studies. To test the validity of the data, data, technique and time triangulation was carried out. While the informants involved school principals, vice principals, teachers, and students. The results of the research show that there is a uniqueness in the implementation of character education through the development of students' spiritual intelligence consistently by all school members and integrated into various school programs. These findings are expected to inspire other schools and related parties in planning and implementing student character education programs